2018
DOI: 10.1098/rsos.180957
|View full text |Cite
|
Sign up to set email alerts
|

The crystal-form transition behaviours and morphology changes in a polyamide 6 cyclic dimer

Abstract: The characteristics of pure α- and β-form of the cyclic dimer (1,8-diazacyclotetradecane-2,9-dione) were systematically and integrally investigated during this study. The results showed that the α-form could dissolve and rapidly transform into the β-form in methanol, and in caprolactam solution at a lower temperature, an interesting transition occurred and formed co-precipitates, which refract colourful light under PLM. However, these dimers can aggregate in water, and they are then transformed into multi-slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Some oligomers can be observed in Figure 9a, which are similar in morphology to the rod-shaped cyclic dimers previously reported in the literature [32]. Most of their directions are the same as the forming direction, and a large amount of oligomers are observed in the cross-section, indicating that too many oligomers will be concentrated in a part of the matrix [32].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Some oligomers can be observed in Figure 9a, which are similar in morphology to the rod-shaped cyclic dimers previously reported in the literature [32]. Most of their directions are the same as the forming direction, and a large amount of oligomers are observed in the cross-section, indicating that too many oligomers will be concentrated in a part of the matrix [32].…”
Section: Resultssupporting
confidence: 78%
“…Approximately 2 wt% of the oligomers contained in PEA are mainly composed of cyclic dimers [12]. In PEA, the cyclic dimer is present in the matrix in the form of a rod [32]. In the uniaxial stretching process, the rod crystal is parallel to the stretching direction.…”
Section: Resultsmentioning
confidence: 99%
“…The interface interaction would suppress the rearrangement of the molecules, limiting intramolecular hydrogen bonding in the intrasheet, while the stacking of the molecules would be favored in the deposition process, which can contribute the intermolecular hydrogen bonding in the γ form. On the other hand, we may also consider that some oligomers, such as the cyclic oligoamides, can form the crystal structure in the deposited thin film. , But, the relevant crystal structures were mainly reported with monodisperse/pure oligomers, and their XRD patterns contain a series of clear peaks from 11° to 23° . Thus, it is proposed that the crystal structure of the deposited thin film may contribute to the polymer components or large number of oligomers of different sizes.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 But, the relevant crystal structures were mainly reported with monodisperse/pure oligomers, and their XRD patterns contain a series of clear peaks from 11°to 23°. 44 Thus, it is proposed that the crystal structure of the deposited thin film may contribute to the polymer components or large number of oligomers of different sizes. Surface/Interface Conditions of the Deposited Thin Film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…If the meta-amide bond is attacked, a cyclic dimer is produced. 9 In addition to water, the production of cyclic oligomers is also affected by the reaction temperature and time. 10,11 Therefore, a few studies have reported that the formation of cyclic oligomers can be reduced by adjusting the polymerization process.…”
Section: Introductionmentioning
confidence: 99%